Design and application of a compact helical air intake system resonator for broadband noise control. (February 2018) - Meriç, Cem; Erol, Haluk; Özkan, Aytekin
Abstract: In this work, we have developed an analytical model that uses the transfer matrix method to predict the transmission loss (TL) of a resonator system with a helical side branch duct connected to the main duct. The resonator system is tuned to the frequency range appropriate for passenger cars that require a decrease in the air intake pipe radiated noise at frequencies less than 1000 Hz. The developed resonator does not require additional volume to fulfill the packaging requirements. The developed helical resonator has been analyzed numerically. The analytical results are first validated with the numerical results. Then, a prototype part has been produced using a rapid prototyping technique. Finally, the prototype part has been tested on a 1.6 l Gasoline Engine Vehicle.